Plasma progesterone and blood metabolite profiles in post-partum small East African Zebu cows - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (Springer, 1993)
Plasma progesterone profiles were used to monitor post-partum reproductive activity in 12 Small East African Zebu (Bos indicus) cows allocated to either supplementary or no supplementary feeding (control) with continious or restricted (twice daily) suckling regimes. Intact bulls were used for breeding. Blood samples were collected 3 times a week for 33 weeks to determine blood metabolite concentrations. Plasma progesterone levels remained below 1 ng/ml until week 12 post-partum. Only 5 cows showed ovarian activity over the 33 week period. Cows that cycled expressed irregular and short-lived progesterone rises lasting 8 to 12 days prior to establishment of normal patterns of progesterone secretion where progesterone levels ranged from 8 to 10 ng/ml in cows with normal cycles. Plasma total protein, albumin, globulin, blood urea nitrogen and glucose levels varied over time without consistent trends, and were not influenced by either supplementary feeding of suckling regimes, nor differed between cyclic and acyclic cows. It was concluded that extended post-partum anoestrus, conception failure and early embryonic mortality were responsible for lowered reproductive efficiency in zebu cows. Blood metabolite concentrations were not good indicators of nutritional status and were not related to post-partum ovarian activity.